PENGARUH MOTIVASI KERJA, IKLIM ORGANISASI DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN MARKETING PADA PT. AGUNG TOYOTA BENGKULU - Pahlawan, Alfi; Onsardi, Onsardi (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
This research aims to determine the effect of work motivation, organizational climate and leadership on the job satisfaction of Marketing Employee at PT. Agung Toyota Bengkulu, both partially and simultaneously. There are several factors that will be discussed in this study, including Work Motivation (X1), Organizational Climate (X2) and Leadership (X3). The object of this research was the marketing employee at PT. Agung Toyota Bengkulu. There were 97 employees. The researcher used the method of data collection by means of observation, questionnaires, and interviews. Several data analysis techniques used Â were the instrument test, classic assumption test, respondent response analysis, multiple linear regression analysis, determinant coefficient, and also hypothesis testing. From the results of the tests that have been carried out it can be concluded that the Work Motivation variable (X1), Organizational Climate (X2) and Leadership (X3) affect partially or simultaneously on Job Satisfaction of Marketing employees at PT. Agung Toyota Bengkulu. From the results of multiple linear regression tests obtained the regression equation is as follows:Y = 2868 + 0.221 (X1) + 0.277 (X2) + 0.231 (X3).Â Keywords: Work Motivation, Organizational Climate, Leadership, Marketing Employee, Job Satisfaction